Edukasi kesehatan reproduksi pada remaja - Susi Widiawati; Selvi Selvi (Jurnal Pengabdian Harapan Ibu (JPHI), 2022)
Adolescent reproductive health must be a special concern, as a tool that serves to prepare offspring. The problems that occur in young women are vaginal discharge, itching and unpleasant odor from the outer reproductive area and in young men they do not maintain cleanliness around their genitals. This activity aims to provide reproductive health education to adolescents and prevent complaints on adolescent reproductive organs. The activity was carried out using the method of providing reproductive health materials to adolescents at SMKN Jambi City in November 2019 with 39 students and grade 1 students as the subject. Activities are carried out with the pre-test stage, the implementation stage of education and discussion as well as the evaluation stage with the post-test. PkM activities with 34.8% pre-test results and 76.91% post-test results. It can be concluded that there is an increase in the knowledge of students and students after education about reproductive health in adolescents is carried out.